The influence of constructive size of equipment on the carbonation process in sugar production - Yushchuk, Inna; Ovcharuk, Vladimir; Seidykh, Olga; Vovkodav (Obizyuk), Natalia (My University, 2015)
The paper studies influence of the size of equipment for saturation in crude juice purifying process in sugar production. Parametric diagrams and a mathematical model for calculation of carbonation process are developed. It is established that theoretical size of saturator is smaller than the size of machines used in sugar factories. Saturation of carbonation gas with carbon dioxide has negative impact on its utilization rate.
Keywords: кафедра інформаційних технологій, штучного інтелекту і кібербезпеки; оптимізація розрахунку; очистка дифузійного соку; цукрове виробництво; оптимизация расчета; очистка диффузионного сока; сахарное производство; calculations optimization; crude juice purifying; sugar production